Adsorption of phosphate from domestic wastewater treatment plant effluent onto the laterites in a hydrodynamic column - Fulazzaky, Mohamad Ali; Khamidun, Mohd Hairul; Md Din, Mohd Fadhil; Mohd Yusoff, Abdul Rahim (Elsevier, 2014)
High concentration of phosphate (PO4 3-) released from wastewater treatment plant effluent (WWTPE) can negatively impact aquatic ecosystems and human health. Even though adsorption techniques have been widely used to remove PO4 3- from waters, an empirical model used to describe the adsorption of PO4 3-onto a porous material is still not yet fully understood. In this study, the empirical models of bed depth service time (BDST), Thomas and mass transfer factor (MTF) are used to scrutinize the adsorption behaviors of PO4 3- removal from a domestic WWTPE onto the granular laterites applied to a hybrid plug flow column reactor. Despite the applications of Thomas and MTF model are verified suitable for use with general-purpose data models, the BDST is only applicable to model the data of monitoring PO4 3- after seeing a more than 50% outflow. The dynamic adsorption capacity, adsorption rate constants and equilibrium solute uptake are determined. The resistance of mass transfer for the adsorption of PO4 3- onto granular laterites in aqueous solution before breakthrough occurred to continue until the outflow reaches at certain percentage is only dependent on porous diffusion. The application of experimentally verified adsorption data binding with three different models can make significant contributions to improving environmental quality